Nutrient efficiencies and their evaluation in 'Bhawani' toria (Brassica rapa var napus) on farmers' fields for prescription-based fertilizer recommendations - SURI, V K; VERMA, T S; PAUL, JAI (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during the winter season of 1994 to work out nutrient requirement per tonne of seed production, efficiency of soil available nutrients and that of applied nutrients to Bhawani toria (Brassica rapa (L.) Theil, emend. Metzger var napus L.; syn B. campestris L. ssp oleifera (Metzger) Sink. var toria) in subhumid sub-tropical zone of Himachal Pradesh (India) along with fertilizer adjustment equations. It was found that for producing 1 tonne of toria seed, 45.0, 3.0 and 31.0 kg N, P and K were required respectively. Contribution of soil-available N to toria was 5% and it was 83.4% for fertilizer. Contribution in case of available P from soil was 13% and 66% from fertilizer. Using above fertilizer equations, 11 field trials were conducted during 1995-2000 at different locations on farmers' fields. Results revealed that it is possible to target toria yield up to 1.5 tonnes/ha.